Altered Microbiota, Impaired Quality of Life, Malabsorption, Infection, and Inflammation in CVID Patients With Diarrhoea - van Schewick, Cornelia M.; Nöltner, Christina; Abel, Svenja; Burns, Siobhan O.; Workman, Sarita; Symes, Andrew; Guzman, David; Proietti, Michele; Bulashevska, Alla; Moreira, Fernando; Soetedjo, Veronika; Lowe, David M.; et al. (Frontiers in Immunology, 2020)
Background: Diarrhoea is the commonest gastrointestinal symptom in patients with common variable immunodeficiency (CVID). Objective: The aim of this study was to describe the prevalence and clinical presentation of chronic and recurrent diarrhoea in the Royal-Free-Hospital (RFH) London CVID cohort, including symptoms, infections, level of inflammation, and microbial diversity. Methods: A cross-sectional study of adult CVID patients (139 out of 172 diagnosed with CVID completed the screening questionnaire). Those with diarrhoea ≥6 days/month had stool and blood samples analysed and completed the short Inflammatory Bowel Disease Questionnaire (sIBDQ). BMI, spleen-size, lymphocytes and gut-microbial diversity were compared. Due to logistical and clinical restraints, not all patients could be analysed on all measures. Results: 46/139 (33.1%) patients had current significant diarrhoea. In patients with past or present diarrhoea, BMI was lower (median 23.7 vs. 26, p = 0.005), malabsorption more common (57.97 vs. 35.71%, p = 0.011). CD4+ lymphocytes were higher in patients with diarrhoea (p = 0.028; n = 138), but CD4+ naïve lymphocytes were significantly higher in non-diarrhoea patients (p = 0.009, N = 28). Nine patients had confirmed or probable current gastrointestinal infections. Calprotectin was >60 μg/g in 13/29 with significant diarrhoea including 9 without infection. SIBDQ revealed a low median score of 4.74. Microbial alpha diversity was significantly lower in CVID patients compared to healthy household controls. There was no significant difference in alpha diversity in relation to antibiotic intake during the 6 weeks prior to providing samples. Conclusion: Patients with CVID and significant diarrhoea had infections, raised calprotectin, malabsorption, a lower BMI, an impaired quality of life (comparable to active IBD), and they differed from non-diarrhoea patients in their lymphocyte phenotyping. Furthermore, microbial diversity was altered. These findings strongly imply that there may be an inflammatory nature and a systemic predisposition to diarrhoea in CVID, which necessitates further investigation.